Keterampilan guru bimbingan dan konseling dalam implementasi metode project based learning pada kurikulum merdeka - Putro, Tegar Bayu; Marisa, Cindy; Fitriyanti, Evi; Utami, Sri (Universitas Indraprasta PGRI, 2023)
the independent curriculum currently being implemented is a curriculum in which there are several updates in teaching systems and methods, such as in the preparation of lesson plans and the formulation of student achievement indicators. This research aims to determine the description of the skills of guidance and counseling teachers at MGBK SMK Kab. Bogor in implementing the Project Based Learning method in the Independent Curriculum. This research uses a quantitative survey method with a questionnaire instrument as a research data collection tool. The research sample was 30 vocational guidance and counseling teachers at MGBK, Bogor Regency. The results of this research provide an illustration that the skills of BK teachers in implementing the PjBL method in the Independent Curriculum at MGBK Vocational Schools in Bogor Regency are in the quite good category with a percentage of 62%. Thus, this research can provide appropriate recommendations and strategies for schools and guidance and counseling teachers to improve skills and competencies in implementing the PjBL method in the Independent Curriculum at MGBK Vocational Schools in Bogor Regency.